2018
DOI: 10.14791/btrt.2018.6.e4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Brain Tumor Induction from Pediatric Head CT Procedures: A Systematic Literature Review

Abstract: Head computed tomography (CT) is instrumental for managing patients of all ages. However, its low dose radiation may pose a low but non-zero risk of tumor induction in pediatric patients. Here, we present a systematic literature review on the estimated incidence of brain tumor induction from head CT exams performed on children and adolescents. MEDLINE was searched using an electronic protocol and bibliographic searches to identify articles related to CT, cancer, and epidemiology or risk assessment. Sixteen stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 43 publications
0
42
0
3
Order By: Relevance
“…Despite these findings appearing reassuring, there is strong epidemiological evidence linking CT scanning in childhood with an increased risk of malignancy. [8,31] Confidently attributing cancer to childhood CT radiation exposure is difficult; however, numerous studies aiming to assess this risk have been published. (Table 1) These include three population studies, reporting patient exposure and outcome data, as well as studies calculating a predicted risk based on the previous population studies or those relating to Japanese Bomb survivors or the BIER reports [8,13,20,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these findings appearing reassuring, there is strong epidemiological evidence linking CT scanning in childhood with an increased risk of malignancy. [8,31] Confidently attributing cancer to childhood CT radiation exposure is difficult; however, numerous studies aiming to assess this risk have been published. (Table 1) These include three population studies, reporting patient exposure and outcome data, as well as studies calculating a predicted risk based on the previous population studies or those relating to Japanese Bomb survivors or the BIER reports [8,13,20,25].…”
Section: Discussionmentioning
confidence: 99%
“…The review identified that a single CT head scan in childhood carries a 2.4-fold increased risk of developing a brain tumour compared to children who have not been exposed to a CT head scan. Whilst the increased relative risk is significant, the estimated risk of developing radiationinduced cancer corresponds to around one per 1800 paediatric head CTs [31].…”
Section: Introductionmentioning
confidence: 99%
“…A head CT in the PED setting is not typically indicated, especially due to substantial radiation exposure and cost-effectiveness considerations. 3 When a child presents to the PED with an acute headache the attending physician will first focus on ruling out emergencies and identifying red flags suggestive of an intracranial tumor, especially if the child presents without fever or signs of meningitis. 4 The next priority is pain management, followed by a decision by the emergency physician whether the patient requires further evaluation or can be discharged home.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that the high number of CTs in our study was not without risk. First, although the cumulative risk of developing a radiation‐induced malignancy later in life was small, the relative risk has been shown to more than double . Second, in our cohort, nontraumatic incidental findings were present in 10% of CT scans not related to MHI.…”
Section: Discussionmentioning
confidence: 99%